THE POTENCY OF BAJAKAH TAMPALA (Spatholobus littoralis Hassk) AN INDIGENOUS INDONESIAN HERBAL MEDICINE : A BIBLIOMETRIC APPROACH - Davit Nugraha; Nurkhasanah; Sapto Yuliani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Bajakah tampala (Spatholobus littoralis Hassk) has significant potential in the pharmaceutical field and could become a source for drug discovery and development in the future. This bibliometric analysis aimed to map existing research to identify novelties and gaps for future studies. The research method involved a literature review using bibliometric analysis, using the keyword "bajakah tampala" in Publish or Perish 8, followed by metadata organization using Mendeley and VOSviewer to map research trends. The research findings indicate that Bajakah tampala exhibits variability and gaps in its antioxidant and anti-inflammatory properties, and there is still limited research on this topic. Further research is needed to establish a link between antioxidant and anti-inflammatory effects. Keywords: Bibliometrics, Bajakah tampala, antioxidants, anti-inflammatory, Publish or Perish (POP), VOSviewer